Week fragmentation of round plates - Brodskii, R.Ye.; Tur, A.V.; Yanovsky, V.V. (Functional Materials, 2012)
The simple model of binary week fragmentation of round plates is considered. It is shown, that distribution function of fragments by masses is depended on choice of fissures arise mechanism. The exact distribution function of fragments by masses is obtained with isotropic and anisotropic fissure spreading in plates and its asymptotic behaviour in small and large masses regions is studied.